2014
DOI: 10.1177/1524839914557862
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Diet for Urban Aboriginal Youth

Abstract: Overweight and obesity are associated with several life-threating comorbidities, including type 2 diabetes and cardiovascular disease. Obesity is a growing health concern in North America, with some groups experiencing higher levels of obesity than others. One group of particular interest is urban Aboriginal youth because they are a quickly growing population who experience high rates of obesity. Obesity is a complex condition with many contributing factors, diet being one of the primary contributors. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…For instance, food may be prioritized over needed medication but not over rent, and people tended to purchase food that was filling rather than nutritious [68]. In Canada, Kerpan et al [71] had similar findings when speaking with urban Indigenous youth, who stated income was the greatest barrier to healthy food purchasing.…”
Section: Affordability Of and Access To Store Foodssupporting
confidence: 63%
See 4 more Smart Citations
“…For instance, food may be prioritized over needed medication but not over rent, and people tended to purchase food that was filling rather than nutritious [68]. In Canada, Kerpan et al [71] had similar findings when speaking with urban Indigenous youth, who stated income was the greatest barrier to healthy food purchasing.…”
Section: Affordability Of and Access To Store Foodssupporting
confidence: 63%
“…In all three countries, for those Indigenous people operating under budget constraints, healthy foods from supermarkets were often unaffordable [60,61,64,65,68,71]. In the Australian context, Foley [68] found that despite the breadth of choices in the food system, the cost of healthy food remained a barrier for many urban Indigenous households.…”
Section: Affordability Of and Access To Store Foodsmentioning
confidence: 99%
See 3 more Smart Citations